MNREGA : Success and Failure - Agarwal, Rakesh Kumar; Chaudhary, Prabhat (Journal of Commerce and Trade, 2011)
Realising the need of generating employment opportunities in the country to achieve a satisfactory rate of employment in the country, Government of India launched the National Rural Employment Guarantee Scheme in September 2005. This Act will provide a legal guarantee for atleast 100 days of employment every year for atleast one adult member (willing to do unskilled manual work) of the rural household. Though the scheme was initially introduced in only 200 districts, it is now functionig in all the districts of the country. The MNREGS is the largest employment programme in the human history. It has completed five years of its implementation and has provided employment to around 40 million rural households. Under Section 4 of the Act, the Scheme to be formulated by the State Governments will conform to the legally non-negotiable parameters laid down in Schedules I and II of the Act. In addition, these Schemes will conform to the operational parameters delineated in the Guidelines. The Scheme so formulated will be called the National Rural Employment Guarantee Scheme (NREGS), followed by the name of the State. The Gram Panchayats, PRIs, District and State Level department personnel involved in implementing NREGS, as well as committees, groups formed for the purpose of vigilance will be monitoring and perform social audit by the Government of India. Social audit is an effective tool for the implementation of NREGS. It is a process which promotes mass awareness and also ensures people’s participation.